Ecological dynamics of spin bowling in test match cricket: A longitudinal analysis of delivery speed between Australia and India. Issue 6 (December 2018) - Crowther, Rian H; Gorman, Adam D; Spratford, Wayne A; Sayers, Mark G; Kountouris, Alex
The purpose of this study was to highlight the effects of the environment on spin bowling tactics in test match cricket. The speed differences employed by Indian and Australian spin bowlers in home and away test matches were examined over a nine-year period. Eleven test matches played in Australia and 10 test matches played in India from 2007 to 2015 were analysed (3413 spin overs). During this time, 12 spin bowlers represented Australia (mean age 28.0 ± 3.7 years) and 13 represented India (mean age 29.1 ± 4.1 years). In each environment, the home team's spin bowlers were more successful than the away team's bowlers. There was no difference in mean delivery speed between the teams when competing in either country's conditions. However, success in Australia was associated with less variability of delivery speed. In contrast, success in India was associated with greater variability of delivery speed. This would suggest that neither team changed this aspect of their delivery tactics to suit the opposition's home environment, demonstrating the difficulty that even elite spin bowlers experience in adapting to unfamiliar conditions. These findings highlight the need for diversity in practice conditions by creating representatively designed learning environments to help spin bowlers acquire the adaptive behaviours required in test match cricket.